Electromagnetic studies of Zvizdal-Zaliska and Brusyliv fault zones of the Ukrainian shield - V. A. Ilyenko; A. M. Kushnir; T. K. Burakhovich (Геофизический журнал, 2019)
Spatial-temporal distribution pattern of geomagnetic variations and electric field in the western part of the Ukrainian shield has been obtained as a result of experimental studies carried out by the methods of deep magnetotelluric sounding and magnetovariational profiling in 2018 along two profiles (15 points). It makes possible to estimate the value of electroconductivity and geoelectric structure of the section along the vertical and horizontal directions. Processing has been conducted with the help of modern software system PRC-MTMV that guarantees joint noise immunity of evaluation of impedance and induction parameters of synchronous МТ/МВ-records. Tipper appraisals have been obtained for the periods of geomagnetic variations from 50 to 3400 s, the curves of apparent resistance and phases of impedance from 20 to 10000 s. The principal result of high quality interpretation of geoelectric studies is revealing of high electro-conductivity anomalies (4 surface ones, 1 subsurface) in the Earth crust with complex system of faults in jointing zone of the Podolia and Rossinsky megablocks. Anomalies are characterized by different electroconductivity, the depth of occurrence and shape. Appraisals obtained with different approaches to formal interpretation of magnetotelluric sounding agree with regional three-dimensional geoelectric model of the western part of the Ukrainian shield and add to the concept on debatable deep structure. Surface anomalies of electroconductivity have been discovered: 1) in the central part of Zvizdal-Zalessky fault zone, 2) between the Pogrebynsky and the Kocherov faults, 3) along the Velykoerchyk and 4) Ulashev faults. Their nature is explained by heightened content of graphite and by ore formation confined to tectono-metasomatic zones. Deep anomaly of electroconductivity has been allocated with its surface projection spatially coinsiding with the area of cross-section of the Brussilov and the Nemyrov fault zones (and mineraginetic zones of the same name). Its upper edge deepens eastward from Zvizdal-Zalessky fault zone. High electroconductivity anomalies are spatially attached to tectonic fault zones and the zones of metasomatic alterations. Their territorial arrangement corresponds to metallogenic ore zones. Therefore they can be used as geoelectric criteria for the search of ore manifestations.